Avoidance of simultaneous patch use in Japanese large-footed bats - Emyo Fujioka; Masashi Shiraishi; Tamao Hirao; Yui Onishi; Dai Fukui; Shizuko Hiryu (PLoS ONE, 2026)
Group foraging can enhance prey detection, but depending on resource availability, it may also generate conflicts among conspecifics. To understand how animals balance these benefits and costs, foraging performance must be evaluated together with inter-individual interactions. However, under fully natural conditions, it remains challenging to quantify both simultaneously. Here, we investigated how individual foraging efficiency and pairwise interactions are shaped when more than one individual simultaneously exploit the same foraging patch, using the Japanese large-footed bat ( Myotis macrodactylus ) as a model system. We monitored an entire pond functioning as a natural foraging patch using two thermal cameras and an eight-channel microphone array, and reconstructed the arrival, prey-attack, and exit times of individual bats. Using a Poisson generalized linear mixed model (GLMM), we found that prey-attack rates were approximately 25% lower during paired flights than during solitary flights. We then constructed a null model in which arrival, attack, and departure events followed independent Poisson processes parameterized from the empirical data. Compared with null-model predictions, both the total duration and the duration of individual paired flights in the empirical data were significantly shorter, indicating that bats limited the time spent co-using the same patch relative to solitary foraging. In addition, the probability that the first exiting individual was the one that arrived earlier or later did not deviate from chance levels, providing no evidence for a prior residence advantage. Together, these results indicate that co-use duration was shorter than expected under the null model regardless of arrival order and was accompanied by a reduced prey-attack rate during simultaneous patch use. These findings suggest that bats tend to avoid prolonged shared patch use, which may help maintain prey-attack efficiency. Our findings highlight bats as an excellent model system for non-invasively linking individual behavior and foraging performance via echolocation, and for elucidating the dynamics of foraging behavior and sensory interference in the wild.